MicroRNA as Biomarkers in Cancer Diagnostics and Therapy - Sempere, Lorenzo F. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue celebrates the 25th anniversary of the discovery of the first microRNA. The size of the microRNome and complexity of animal body plans and organ systems suggests a role for microRNAs in cell fate determination and differentiation. More than 2000 sequences have been proposed to represent unique microRNA genes in humans, with an increasing number of mechanistic roles identified in developmental, physiological, and pathological processes. Thus, dysregulation of a few key microRNAs can have a profound global effect on the gene expression and molecular programs of a cell. This great potential for clinical intervention has captured the interest and imagination of researchers in many fields. However, very few fields have been as prolific as the field of cancer research. This Special Issue provides but a glimpse of the large body of literature of microRNA biology in cancer research, containing 4 original research studies and 4 review articles that focus on specific hematologic or solid tumors in disease. Collectively, these articles highlight state-of-the-art approaches and methodologies for microRNA detection in tissue, blood, and other body fluids in a range of biomarkers applications, from early cancer detection to prognosis and treatment response. The articles also address some of the challenges regarding clinical implementation.